ANALISIS HUKUM PENERAPAN ANTI PENCUCIAN UANG TERHADAP KEBIJAKAN RAHASIA BANK - Vediani, Ilmi (Veritas et Justitia, 2016)
This article discusses money laundering and the implementation of Customer Due Diligence (CDD) which is to be understood as part of the effort to eradicate this particular crime. Money laundering is not an autonomous crime but is always related or stems from an original crime (predicate crime). This crime is committed habitually using financial institution or banks as its instrument.  One factor making this possible is the obligation of bank to guard and maintain customer’s trust by virtue of bank’s secrecy. Nonetheless, this bank secrecy can be waived. By virtue of CDD, banks are under the obligation to implement a process of customer identification, including verification- monitoring of customers financial transaction or activities. In the case, they detect suspicious financial transactions the banks are under the obligation to report their findings to the Indonesian Financial Transaction Reports and Analysis Centre (INTRAC) and/or law enforcement officers Keywords: money laundering, bank, customer due diligence, anti-money laundering program and bank secrecy